The Influence of The Project Based Learning (PjBL) Model on Biology Learning Outcomes of Class X Students of SMAS PGRI Sungguminasa on Environmental Change Material - Ramadhani, Andi Annisa Putri; Arsal, Andi Faridah; Palennari, Muhiddin (Biology Teaching and Learning, 2023)
Abstract. This study aims to determine the effect of the application of the Project Based Learning model on the biology learning outcomes of the tenth graders of SMAS PGRI Sungguminasa on the material of environmental change. This type of research is a quasi-experimental (quasi-experimental). The population in this study were all students of class X SMAS PGRI Sungguminasa with a research sample of 53 students. Data collection techniques using the test method. The results showed that learning outcomes using the Project Based Learning model obtained an average value of 78.20. While the conventional learning model obtained an average value of 64.29. And there is an effect of the Project Based Learning model on the biology learning outcomes of class X students of SMAS PGRI Sungguminasa.Keyword : Project Based Learning (PjBL), learning outcome.